Microprocessor control system of the electroontact surfacing with two roller electrodes - Чепель, Юлия Анатолиевна; Бережная, Елена Валерьевна; Кассов, Валерий Дмитриевич (Інститут енергетичних машин і систем ім. А. М. Підгорного Національної академії наук України, 2014)
Electrocontact surfacing is a complex electrothermal process with the relationship between the parameters, the change nature of which in the real conditions depends on a number of factors, which during the welding current pulse change over a wide range. At the electrocontact surfacing with powdered electrodes, the change in physical properties of materials in the surfacing zone will be especially significant since during the heating process the compaction, sintering, melting of charge ingredients of the core takes place that, as a result, has the impact on the surface layer characteristics on the whole. Therefore, it is expedient to build the high-speed system of measurement, registration and control of process parameters. The microprocessor control system of the electrocontact surfacing with two roller electrodes was developed, the use of which allows to adjust the key process parameters in real time in order to increase the surfacing efficiency and ensure optimal surfacing-technological characteristics and quality of wear-resistant layer, surfaced on the effective area of the part.